Revision Total Knee Arthroplasty for the Management of Periprosthetic Fractures. Issue 9 (September 2017) - Kuzyk, Paul R.T.; Watts, Evan; Backstein, David
Abstract : Periprosthetic fractures after total knee arthroplasty (TKA) can present reconstructive challenges. Not only is the procedure technically complex, but patients with these fractures may have multiple comorbidities, making them prone to postoperative complications. Early mobilization is particularly beneficial in patients with multiple comorbidities. Certain patient factors and fracture types may make revision TKA the ideal management option. Periprosthetic fractures around the knee implant occur most frequently in the distal femur, followed by the tibia and the patella. Risk factors typically are grouped into patient factors (eg, osteoporosis, obesity) and surgical factors (eg, anterior notching, implant malposition). Surgical options for periprosthetic fractures that involve the distal femur or proximal tibia include reconstruction of the bone stock with augments or metal cones or replacement with an endoprosthesis.